HipHop und Postkolonialismus - David Chemeta (Recherches Germaniques)
This article analyzes the use of foreign languages in German hip hop from the perspective of postcolonial theories, replacing the tensions between colonizers and colonized with symbolic power struggles between “dominant” and “dominated”. More precisely, I try to show how the history of German hip hop has evolved from the exclusive use of the English language viewed as a “universal language”, to the use of the German language, and then “creolization” and a linguistic bricolage between German, Turkish, and other languages. By analyzing the linguistic evolutions of hip hop in Germany using concepts from Postcolonial Studies, I seek to highlight the way many rappers with migration backgrounds, as well as part of the people from migration backgrounds living in Germany, have deconstructed the classical idea of “germanity”, often in order to reshape it into a more hybrid form.